(untitled) (Biological Sciences - PJSIR, 2001)
Studies were made on the performance of a coccinel lid predator, Menochilus sexmaculatus (Fab.) for the control of potato aphid, Myzus persicae (Su l zer). The dai l y feed i n g of M . sexmaculatus l arvae increased with age and reach ed a maxi mu m (30.72) aphids) on the 6th clay. The rate of aphid con sum ption declined at pu pal i niti ati on . The predator showed a density dependent respon se both at the larval and the adult stages. Fi ve l arvae of M. sexmaculatus consumed 80.67% and 90.63% of aph ids in caged potato plants i n 72 hours when released on 1 50 and 160 aphids, respecti vely. In contrast, the adu l t beetles consumed 98.25% and 94.25% of potato aphids in 72 hours when the rel ease was made on 80 and 1 25 aphids respectively. Wh en the number of aphids was 170 at release time, th e adult and larvae reduced the aphid population by 69.53% and 67.65% respectivel y.